2022
DOI: 10.3389/fpls.2021.802664
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Shifted Vegetation Phenology on Runoff Across a Hydroclimatic Gradient

Abstract: Climate warming has changed vegetation phenology, and the phenology-associated impacts on terrestrial water fluxes remain largely unquantified. The impacts are linked to plant adjustments and responses to climate change and can be different in different hydroclimatic regions. Based on remote sensing data and observed river runoff of hydrological station from six river basins across a hydroclimatic gradient from northeast to southwest in China, the relative contributions of the vegetation (including spring and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 59 publications
1
6
0
Order By: Relevance
“…Recent studies have increasingly focused on the effect of vegetation phenology and growth on runoff. It is found that earlier spring phenology and delayed autumn phenology promote a longer growing season and can increase the period for plant transpiration, potentially resulting in larger transpiration and might reduce the river runoff (Piao et al, 2019;Geng et al, 2020;Wu et al, 2012;Chen et al, 2022). These results were consistent with the negative effect of the intra-annual temporal pattern of LAI associated with the phenology change on runoff simulated by the VIC model, considering explicit vegetation dynamics in this study.…”
Section: Potential Driving Mechanisms Of Temporally Change Of Laisupporting
confidence: 88%
See 1 more Smart Citation
“…Recent studies have increasingly focused on the effect of vegetation phenology and growth on runoff. It is found that earlier spring phenology and delayed autumn phenology promote a longer growing season and can increase the period for plant transpiration, potentially resulting in larger transpiration and might reduce the river runoff (Piao et al, 2019;Geng et al, 2020;Wu et al, 2012;Chen et al, 2022). These results were consistent with the negative effect of the intra-annual temporal pattern of LAI associated with the phenology change on runoff simulated by the VIC model, considering explicit vegetation dynamics in this study.…”
Section: Potential Driving Mechanisms Of Temporally Change Of Laisupporting
confidence: 88%
“…6). Since phenology determines the start and end time of vegetation growth and is highly sensitive to climate change (Liang and Schwartz, 2009;Fu et al, 2019), climate warming has played an important role in advancing the spring phenology and delaying autumn phenology, and consequently extended the length of the vegetation growing period across the globe (Piao et al, 2019;Menzel et al, 2020), especially for the semiarid and semihumid regions of China (Wu et al, 2016;Chen et al, 2022). In addition, the variations in micro-topography from slope land into flat terrace significantly increase soil moisture (Bai et al, 2019), which could also inevitably alter interannual change and intra-annual temporal pattern of LAI.…”
Section: Potential Driving Mechanisms Of Temporally Change Of Laimentioning
confidence: 99%
“…Future investigations for vegetation phenology could pay more attention to the following aspects: (1) Previous studies have focused on the response of vegetation phenology to climate change, while the feedback of vegetation phenology on the climate system is relatively rare and thus need more investigations (Penuelas et al, 2009). In addition, recent studies found that the hydrological cycle was also tightly associated with vegetation phenology (Chen et al, 2022;Geng et al, 2020), but its mechanisms are still largely unclear. Therefore, the effects of vegetation phenology on eco-hydrological processes at global and watershed scales need further studies.…”
Section: Prospects For Vegetation Phenology Researchmentioning
confidence: 99%
“…On the other, key hydrological fluxes and states such as evapotranspiration (ET), soil moisture content and runoff generation are critically dependent on the structures and dynamics of plant communities (Brown et al, 2010; Gerten et al, 2004). For example, runoff is significantly affected by plant‐related processes and factors such as canopy interception (Tao et al, 2020), rooting strategy (Collins & Bras, 2007), leaf area (Zhai & Tao, 2021), phenology (Chen et al, 2022), and transpiration (Li et al, 2020). Likewise, afforestation and the recovery of forests from disturbances could reduce runoff by increasing ET, whereas deforestation often increases runoff (Sun et al, 2006).…”
Section: Introductionmentioning
confidence: 99%